2018
DOI: 10.1042/ebc20180028
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule nucleation by γ-tubulin complexes and beyond

Abstract: In this short review, we give an overview of microtubule nucleation within cells. It is nearly 30 years since the discovery of γ-tubulin, a member of the tubulin superfamily essential for proper microtubule nucleation in all eukaryotes. γ-tubulin associates with other proteins to form multiprotein γ-tubulin ring complexes (γ-TuRCs) that template and catalyse the otherwise kinetically unfavourable assembly of microtubule filaments. These filaments can be dynamic or stable and they perform diverse functions, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
141
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(144 citation statements)
references
References 140 publications
3
141
0
Order By: Relevance
“…GCP4 is organized into two -helical bundles containing the conserved -tubulin r ing complex i nteracting p rotein motif 1 (GRIP1, corresponding to the N-domain) and the GRIP2 (C-domain) motifs 22 . Notably, GCP4 has also been proposed to form part of a -TuSC-like subcomplex at the -TuRC "overlap" 17,23,24 . Surprisingly, however, the crystallographic model for GCP4 could not be rigid-body fitted and refined into the -TuRC density map at the "overlap" region (i.e., positions 1 or 14; also referred to as the -TuRC "seam" 25 Further, we aligned our refined GCP4 model to the monomeric, crystallographic GCP4 model via their N-domains 22 , which revealed that within the -TuRC the GCP4 C-domain is rotated by ~10° towards the preceding subunit ( Figure S4F), and helix 21 is rotated by ~90° towards the GCP4-associated -tubulin ( Figure S4G).…”
Section: Main Textmentioning
confidence: 99%
“…GCP4 is organized into two -helical bundles containing the conserved -tubulin r ing complex i nteracting p rotein motif 1 (GRIP1, corresponding to the N-domain) and the GRIP2 (C-domain) motifs 22 . Notably, GCP4 has also been proposed to form part of a -TuSC-like subcomplex at the -TuRC "overlap" 17,23,24 . Surprisingly, however, the crystallographic model for GCP4 could not be rigid-body fitted and refined into the -TuRC density map at the "overlap" region (i.e., positions 1 or 14; also referred to as the -TuRC "seam" 25 Further, we aligned our refined GCP4 model to the monomeric, crystallographic GCP4 model via their N-domains 22 , which revealed that within the -TuRC the GCP4 C-domain is rotated by ~10° towards the preceding subunit ( Figure S4F), and helix 21 is rotated by ~90° towards the GCP4-associated -tubulin ( Figure S4G).…”
Section: Main Textmentioning
confidence: 99%
“…Microtubule nucleation in cells is spatially and temporally controlled to ensure proper cytoskeleton function. The major nucleator is the γ-tubulin ring complex (γTuRC) in which several γ-tubulin complex proteins (GCPs) arrange 14 γ-tubulins into a helical arrangement so that they can serve as a template for microtubule nucleation Tovey and Conduit, 2018). The structure of γTuRC is best understood in budding yeast where 7 smaller 'Y-shaped' γTuSC complexes, each consisting of 2 γ-tubulins and one copy of GCP2 and GCP3, assemble into a conically shaped assembly upon recruitment to spindle the pole body by SPC110 (Kollman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Microtubule (MT) nucleation by the g-tubulin complex (g-TuC) depends on a variety of accessory proteins that regulate g-TuC localization, activity, and assembly state (Farache et al, 2018;Kollman et al, 2011;Lin et al, 2015;Paz and Luders, 2018;Petry and Vale, 2015;Roostalu and Surrey, 2017;Tovey and Conduit, 2018). The core element of the g-TuC, the highly conserved heterotetrameric g-tubulin small complex (g-TuSC), contains two copies of g-tubulin and one copy each of the related proteins GCP2 and GCP3 (in humans).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila melanogaster, Aspergillus nidulans, and fission yeast Schizosaccharomyces pombe), these non-core proteins contribute only modestly to MT nucleation in vivo (Anders et al, 2006;Fujita et al, 2002;Venkatram et al, 2004;Verollet et al, 2006;Xiong and Oakley, 2009), and in other organisms (e.g. budding yeast Saccharomyces cerevisiae), such non-core proteins are completely absent (Lin et al, 2015;Tovey and Conduit, 2018). This diversity has suggested that in addition to the "classical" g-TuRC of metazoan cells, there may be other mechanisms by which multiple g-TuSCs can assemble to generate the functional equivalent of a g-TuRC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation